The Role of Family in Social Harmony: In the Light of Islamic Sharia’h and Pakistani Society - Dr. Hafiz Falak Shair Fazi; Dr Muhammad Hamza; Ibad ur Rehman; Anwar ul Haq; Dr. Hafiz Faiz Rasool; Abbas Ali Raza (Al-Qanṭara, 2022)
Abstract The Creator has created mankind from a couple, which is the basic Unit of society. This couple has different names in which Husband and Wife is more famous. A male and a female get start their life together in the result of an agreement which is known as Nikah in Muslim society. They not only fulfil their physical need from each other but take a lifetime responsibility of their kids as well. They both need proper guideline to fulfil this responsibility in a good manner. In this context, the divine revelation, in shape of Quran & Sunnah, has laid logical, golden and most beneficial teachings in a great detail for this Unit. Actually, this Unit, family, has a great role and importance in the stability and disability of society. Elucidatory, family has different roles likewise Social, Economic, Political, Religious and Ethical role. Unavoidable, a stable, educated, organized and morally equipped family is mandatory for an organized and stable society. So, harmony and affection in husband and wife plays vital role in Social Harmony. In this Article, Pakistani Society will be observed and analyzed in the light of Islamic teachings.